Pemanfaatan Limbah Kayu Ulin (Eusideroxylon zwageri) sebagai Bahan Pengawet untuk Mencegah Serangan Rayap Kayu Kering pada Kayu Jabon (Anthocephalus cadamba) - Karti Rahayu Kusumaningsih; Didik Surya Hadi; Agnestya Erica Sebriliani (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2023)
Eusideroxylon zwageri wood is a type of wood wich have high natural durability that contains extractive compounds such as alkaloids, tannins, saponins, flavonoids, and phenolics that are toxic to wood-destroying organisms. The ironwood sawmill industry produces waste in the form of sawdust that has not been used but only disposed of into the environment. Therefore, that wood sawdust waste can be used as a natural wood preservative to preserve wood whish have low natural durability such as Anthocephalus cadamba. In this study, A. cadamba wood preservation was carried out with irondust extract with various solution formulas, namely 5%, 10%. 15% and 20%. The purpose of this study was to know the effect of irondust extract solution formula as a preservative on the results of jabon wood preservation which includes absorption and retention of preservatives, mortality of dry wood termites, and the percentage of weight reduction of test samples after being fed to dry wood termites. The results of this research showed that the irondust extract solution formula had a significant effect on the absorption and retention of preservatives and the mortality of dry wood termites. The 20% irondust extract solution formula resulted in a higher preservative retention and drywood termite mortality value than the 5%, 10% and 15% solution formula, which was 12.13 Kg/m3 for retention and 88% for drywood termite mortality.